Usaha Penggorengan Kerupuk Pasir Sebagai Sumber Belajar Berbasis Etnopedagogi - Indarwati, Erna Eka; Widodo, Wahono; Istig’faroh, Nurul (CV. Kurnia Grup, 2024)
Sand-frying of crackers is a traditional technique that has been used for a long time, especially in several regions of Indonesia. This method is unique because it uses sand as a heat transfer medium for frying crackers, instead of oil. This research aims to document the traditional process of sand-frying crackers as a form of cultural heritage preservation and to combine traditional knowledge with modern technology to create unique and value-added cracker product innovations. This research uses a qualitative descriptive method. Qualitative methods are research methods that focus on in-depth observation to understand social phenomena, events, and individuals. The data collection techniques used by the researcher are: (1) In-depth interviews, a data collection technique conducted through question-and-answer sessions between the researcher and the informant. (2) Observation, a data collection technique through observation and recording of the object being studied. (3) Documentation, collecting information from various written sources, such as books, journal articles, and local publications. When conducting interviews, the researcher not only recorded the answers from the informants. From this research, it was found that the sand-frying process gives a unique flavor to the crackers that is different from frying using oil and that crackers fried with sand have a much lower oil content compared to crackers fried with oil. This makes sand-fried crackers a healthier alternative. Sand-frying crackers is a cultural heritage that needs to be preserved. Crackers fried with sand tend to have a crispier texture, are more durable, and have a much lower oil content compared to crackers fried with oil. This makes sand-fried crackers a healthier and more attractive alternative for health-conscious consumers. By developing this method, we also preserve traditional knowledge and skills.